(untitled) (Altre Modernità, 2016)
In this paper I analyse how the narrative discourse about the presumed specific characteristics of Portuguese colonization in Brazil moulded racism in Brazil and Portugal. Recently in Portugal there have been episodes of police violence against black people. These episodes have to be considered not only as the product of contemporary racism and its links with neoliberalism effects on marginalized groups, but also as the product of racist and colonial Portuguese ideology. In the case of Brazil, Portuguese colonization is a key element to comprehend the national ideology of mestiçagem, and the false idea of inclusion of African descendants in Brazilian culture that it conveys. The restrictive valorisation (Guillaumin, 1972) of black and indigenous people presents in Brazilian racist ideology is in effect rooted in the Portuguese model of colonization which has been represented as more “human” since the slavery time. Portuguese men are been described as particularly open to mingle with colonized people, especially women, of other cultures and “races”. The notion of lusotropicalism, with its celebrating spirit, has contributed to establish this representation and it has legitimized Portuguese colonization and exploitation also in Africa. These harmful representations of Portuguese colonization and lusotropicalism ideology have thus produced the double effect of negating racism in both Brazil and Portugal.